CURRICULUM DEVELOPMENT MANAGEMENT OF AMANATULLAH BANYUWANGI MADRASAH DINIAH AND ITS RELEVANCE IN THE SCOPE OF NATIONAL EDUCATION - Muhammad Ghafar (Sekolah Tinggi Agama Islam Nahdlatul Ulama Madiun, 2021)
This article results from field research that reveals the implementation of the Madrasah Dinah Amanatullah Banyuwangi curriculum and its relevance within the scope of national education. In this study, data analysis was carried out from the time of data collection, checked again to ensure the validity of the data. The results of the study concluded that the implementation of the madrasah diniah curriculum management in the Amanatullah Islamic boarding school Banyuwangi, was carried out by; involve all parties in planning, implementation, and organization; lastly, by evaluating the curriculum. Involving stakeholders in setting goals, selecting educational experiences (learning), determining the subject matter, organization and integration, and evaluation is known as p development of a decentralized grassroots model of curriculum. This model allows competition in improving the quality and education system nationally, giving birth to humans who are more independent and creative.